Phase transition in a static granular system - Schröter, Matthias; Radin, Charles; Swinney, Harry L.; Nägle, Sibylle (EPL - Europhysics Letters, 2007)
We find that a column of glass beads exhibits a well-defined transition between two phases that differ in their resistance to shear. Pulses of fluidization are used to prepare static sedimented states with well-defined particle volume fractions phi in the range 0.57-0.63. The resistance to shear is determined by slowly inserting a rod into the column of beads. Force measurements and bed height measurements both indicate that the transition occurs at phi = 0.60 for a range of speeds of the rod. Copyright (C) EPLA, 2007.